THE EVALUATION OF LAND AREA MEASUREMENT USING GPS TECHNOLOGY - Vikky Aprelia Windarni; Eko Sediyono; Adi Setiawan (Jurnal Ilmiah Kursor, 2017)
The use of GPS is now widely used by various parties, especially in determining the positionof object location. GPS can be used to measure the land areas, on both wide and flat areas.It can also be used both at night and day, and even it can be used in bad weather conditions.This paper discusses the evaluation of the measurement result of land area using GPStechnology compare to the information containing on the land certificate document. Thegenerated GPS coordinates will be converted into units of meter so that length of each sidecan be known. Heron formula is used to calculate the area of a land plotted on the GoogleMap. From the series of measurement, GPS measurement fall above the land area expressedin the certificate and bellow the meter tape measurement. This measurement still need tostudy further to get a stable measurement. But it can be used by public community to showthe land location to facilitate the land trading. The limitation that must be considered inusing GPS is that GPS signal should not be hindered by any barriers such as leafy trees ortall buildings.